Identification and Validation of Nebulized Aerosol Devices for Sputum Induction - Warren J Davidson; John Dennis; Stephanie The; Belinda Litoski; Cora Pieron; Richard Leigh (Canadian Respiratory Journal)
BACKGROUND: Induced sputum cell counts are a noninvasive and reliable method for evaluating the presence, type and degree of airway inflammation in patients with asthma. Currently, standard nebulizer devices used for sputum induction in multiple patients are labelled as single-patient devices by the manufacturer, which conflicts with infection prevention and control requirements. As such, these devices cannot feasibly be used in a clinical sputum induction program. Therefore, there is a need to identify alternative nebulizer devices that are either disposable or labelled for multi-patient use.